2007
DOI: 10.1074/jbc.m610977200
|View full text |Cite
|
Sign up to set email alerts
|

Light Chain 1 of Microtubule-associated Protein 1B Can Negatively Regulate the Action of Pes1

Abstract: Pes1 was first identified as the locus affected in the zebrafish mutant pescadillo, which exhibits severe defects in gut and liver development. It has since been demonstrated that loss of Pes1 expression in mammals and yeast affects ribosome biogenesis, resulting in a block in cell proliferation. Pes1 contains a BRCA1 C-terminal domain, a structural motif that has been shown to facilitate protein-protein interactions, suggesting that Pes1 has binding partners. We used a yeast two-hybrid screen to identify puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
4
0
3
Order By: Relevance
“…It is required for the late maturation of the 18S and 5.8S rRNA of the pre-40S ribosomes and for maturation of the 25S and 5.8S rRNA of the pre-60S ribosomes (Oeffinger et al, 2004). Pescadillo homolog is a component of the PeBoW complex, which is required for maturation of 28S and 5.8S ribosomal RNAs and formation of the 60S ribosome (Lapik et al, 2004;Lerch-Gaggl et al, 2007). The ribosome biogenesis protein YTM1 is a part of the NOP7 complex, which is required for maturation of 25S and 5.8S ribosomal RNAs and formation of the 60S ribosome (Miles et al, 2005;Tang et al, 2008;Baßler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is required for the late maturation of the 18S and 5.8S rRNA of the pre-40S ribosomes and for maturation of the 25S and 5.8S rRNA of the pre-60S ribosomes (Oeffinger et al, 2004). Pescadillo homolog is a component of the PeBoW complex, which is required for maturation of 28S and 5.8S ribosomal RNAs and formation of the 60S ribosome (Lapik et al, 2004;Lerch-Gaggl et al, 2007). The ribosome biogenesis protein YTM1 is a part of the NOP7 complex, which is required for maturation of 25S and 5.8S ribosomal RNAs and formation of the 60S ribosome (Miles et al, 2005;Tang et al, 2008;Baßler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…38 Previous studies have demonstrated that MAP1B-LC1 interacts with Pes1 and p53 to modulate cell proliferation and apoptosis. 39,40 Thus, loss of function of this gene may contribute to the cancer cell’s ability evade death signals and proliferate. Together, silencing of CCDC37 and MAP1B during development of COPD may contribute to the development of malignant NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that MAP1B not only forms cross‐links between individual microtubules for stabilizing microtubule structure but can also interact with non‐microtubule‐associated proteins that can regulate microtubule stability [2]. It has been also reported that MAP1B has other novel functions [17]. One novel function of MAP1B‐LC1 is that it interacts with Pes1 and induces a cytoplasmic sequestration of nucleolar Pes1, which results in a reduction of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…MAP1B directly binds with glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH), essential in the local energy provision of cytoskeletal structures, and helps to keep this enzyme in close proximity to the cytoskeleton [16]. Recently, MAP1B‐LC1 has also been identified as an interacting partner of Pes1, which is required for ribosome biogenesis and cell proliferation [17]. The interaction with MAP1B‐LC1 induces a cytoplasmic sequestration of nucleolar Pes1, which results in a reduction of cell proliferation.…”
Section: Introductionmentioning
confidence: 99%